Continental Sediments of Cinambo Formation in the Bogor Trough West Java, Indonesia - Abdurrokhim; Iyan Haryanto (UIR PRESS, 2025)
Volcanoclastic sediments commonly represent low quality reservoir facies, since volcaniclastics are composed largely of reactive and unstable minerals that leads to the destruction of porosity by cementation and compaction processes. During the Neogene time, although the Bogor Trough largely infilled by volcaniclastic deep-water deposits, the arenites that delivered from continental in the north actually still contributed as sequel Paleogene deposits. This manuscript intends to discusses the Neogene provenance of continental sediments into the Bogor Trough. The samples are taken from sandstone beds of the Cinambo Formation at Cilutung River in Majalengka. Quartz-rich sandstones are better potential reservoirs in term of quality in hydrocarbon exploration of sub-volcanic region in this area.